Acute thrombosis of left subclavian artery in association with abnormal uterine bleeding: an interesting case report - Jose, Ashwin Antony; A., Padma; Archana, Naidu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Subclavian artery thrombosis arises secondary to damage to the intimal layer of the vessel along with occlusion of blood flow. Etiological factors include atherosclerosis, diabetes, hypertension, arteritis, inflammation due to radiation exposure, compression syndromes, fibro muscular dysplasia. The aim of the study is to determine the association between acute thrombosis of left subclavian artery and abnormal uterine bleeding in a perimenopausal woman. Patient usually presents with upper limb claudication and upper extremity pain at rest. Complications: coronary artery disease, transient ischemic attack, cerebrovascular ischemia or infarct. Diagnosis is by duplex ultrasonography, computed tomography angiography and magnetic resonance angiography. Endovascular intervention is the best modality currently available for relieving subclavian artery thrombosis including percutaneous transluminal angioplasty with stenting or ballooning. Uncontrolled diabetes could be the etiological factor of extensive thrombosis in a patient presenting with abnormal uterine bleeding leading to severe anemia. Severe iron-deficiency anemia with thrombocytosis may be a risk factor for thrombus formation.